PENGGUNAAN BLOCKCHAIN DALAM AKUNTANSI DAN KAITANNYA DENGAN AKUNTABILITAS: SYSTEMATIC LITERATURE REVIEW - Windy Sulistiawati; Totok Dewayanto (Diponegoro Journal of Accounting, 2025)
The development of digital technology has brought blockchain as a significant innovation that has transformed various sectors, including accounting. Although initially known as a technology supporting cryptocurrency, blockchain is now seen as an innovation capable of improving efficiency, transparency, and accountability in accounting systems. This study aims to analyze how blockchain is used in accounting practices and to what extent this technology influences accountability aspects, both in financial, social, and environmental contexts.This study employs a Systematic Literature Review (SLR) method based on a descriptive qualitative approach. Data were obtained from 2,185 articles in Scopus, which were then filtered based on inclusion-exclusion criteria, resulting in 42 relevant articles. Analysis was conducted using NVivo 12 software to identify key themes and systematically synthesize findings.The results of the study indicate that blockchain has great potential to revolutionize accounting systems, particularly through triple-entry recording, audit automation, the use of smart contracts, and improved data integrity and security. Additionally, this technology promotes operational cost efficiency, reduces the potential for fraud, and demands a transformation in the roles of accountants and auditors. Although the adoption of this technology faces several challenges, the benefits it offers present a significant opportunity to enhance accountability in financial reporting and business processes overall.